Modification of carbon support to enhance performance of direct methanol fuel cell - Park, Chan Hee; Scibioh, M. Aulice; Kim, Hyoung-Juhn; Oh, In-Hwan; Hong, Seong-Ahn; Ha, Heung Yong (ELSEVIER, 2006)
Carbon black powder is modified by applying a coating of a proton-conducting polymer electrolyte (ionomer), namely, perfluorosulfonic acid. The carbon is intended for use as a catalyst support in the preparation of Pt-Ru catalysts for direct methanol fuel cell. The aim is to extend the interfacial area between the catalytic metal particles and the proton-conducting ionomer. Ionomer incorporation is found to reduce the micropore volume and thus the BET surface-area of the carbon. Single-cell performance tests on a DMFC show that Pt-Ru catalyst supported on modified carbon exhibits superior performance to that on plain carbon. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: GAS-DIFFUSION ELECTRODES; CATALYST LAYER; NAFION CONTENT; OXIDATION; PLATINUM; MICROSTRUCTURE; SIZE